C++ Unveiled: A Scholarly Expedition into the Integration of Procedural and Object-Oriented Paradigms - Vadiyala, Vishal Reddy (Engineering International, 2022)
C++ is a programming language famous for its diversity, efficiency, and durability. C++, an extension of C, lets developers construct efficient, modular, high-performance Code by combining procedural and object-oriented concepts. This comprehensive C++ language guide covers its fundamentals, advanced capabilities, and real-world applications. Advanced C++ technologies like templates and the Standard Template Library (STL) are explored to learn generic programming and use pre-built components for productivity. Exception handling is simplified with comprehensive error management and best practices. This article guides us through C++’s journey from the C language to its current status as a powerful, versatile programming tool. This guide is for developers who want to learn C++ and use it in various programming applications, not only beginners.